2016
DOI: 10.1002/anie.201607261
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Chemical‐Shift Dispersion of Unstructured Proteins with a Covalent Lanthanide Shift Reagent

Abstract: The study of intrinsically disordered proteins (IDPs) by NMR often suffers from highly overlapped resonances that prevent unambiguous chemical-shift assignments,a nd data analysis that relies on well-separated resonances.W ep resent ac ovalent paramagnetic lanthanide-binding tag (LBT) for increasing the chemical-shift dispersion and facilitating the chemical-shift assignment of challenging, repeat-containing IDPs.Linkage of the DOTA-based LBT to ac ysteine residue induces pseudo-contact shifts (PCS) for resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…In support of the second hypothesis, namely that TNPO1 interferes with phase separation of FUS by interacting with arginines in the C-terminal RGG3-PY domain, we have previously shown that TNPO1 directly binds to a synthetic FUS-RGG3 peptide (Dormann et al, 2012) and to several arginine residues in the FUS-RGG3 region (R472, R473, R476) (Gö bl et al, 2016). This interaction appears to be mainly charge-driven, as we observed a strong decrease in binding of TNPO1 to RGG3-PY at higher salt concentration ( Figure S4A and Table S1).…”
Section: Molecular Mechanisms Contributing To Chaperoning Of Fus By Tmentioning
confidence: 77%
“…In support of the second hypothesis, namely that TNPO1 interferes with phase separation of FUS by interacting with arginines in the C-terminal RGG3-PY domain, we have previously shown that TNPO1 directly binds to a synthetic FUS-RGG3 peptide (Dormann et al, 2012) and to several arginine residues in the FUS-RGG3 region (R472, R473, R476) (Gö bl et al, 2016). This interaction appears to be mainly charge-driven, as we observed a strong decrease in binding of TNPO1 to RGG3-PY at higher salt concentration ( Figure S4A and Table S1).…”
Section: Molecular Mechanisms Contributing To Chaperoning Of Fus By Tmentioning
confidence: 77%
“…Studies with different Ln(III) ions also revealed no change in the isomer ratios, dismissing the influence of metal ion size. Besides MRI, the control of the stereoisomerism of the complexes is also very important for some other applications: The stereoisomeric purity of chiral luminescent lanthanide complexes are crucial for circularly polarised luminescence (CPL) applications 30 , 40 ; Such rigid paramagnetic complexes are also ideal pseudocontact shift tags for proteins for NMR studies in solution and even in cells 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A straightforward application of paramagnetic tagging is the additional dispersion induced by PCS. Paramagnetic tags have already been used to disperse resonances of an intrinsically disordered protein, presenting a crowded amide proton spectrum (Gobl et al 2016 ). Our data demonstrate again that additional dispersion is also relevant for folded, larger proteins that are being studied with methyl group NMR probes, because two-dimensional spectra usually show considerable crowding for methyl resonances in the 1 H region of 0.8–1.0 ppm, as was reported and used before (Sattler and Fesik 1997 ).…”
Section: Discussionmentioning
confidence: 99%